Soft Human–Machine Interface with Triboelectric Patterns and Archimedes Spiral Electrodes for Enhanced Motion Detection. (18th June 2021) - Guo, Hang; Wang, Haobin; Xiang, Zehua; Wu, Hanxiang; Wan, Ji; Xu, Chen; Chen, Haotian; Han, Mengdi; Zhang, Haixia
Abstract: The rapid development of electronic skins has allowed novel multifunctional human–machine interaction interfaces, especially in motion interaction sensors. Although motion sensing is widely used in advanced flexible electronic devices through the integration of single sensing units, the number of electrodes has increased with the increase in integration by the square multiple. This paper presents a self‐powered electronic skin based on the Archimedes spiral structure design, which can detect the multi‐directional movement of the slider without external energy supply. As the rotation angle of the Archimedes spiral increases from 2π to 4π, the maximum resolvable movement direction of the device increases from 24 to 280, and the number of electrodes is kept at 4. Through the exploration of the principle of triboelectricity, the inherent electronegativity of the triboelectric materials is used as the basis for signal discrimination, which not only increases the reliability of the device, but also solves the problem of energy supply during device operation. A reduced number of electrodes and its battery‐free nature enables this electronic skin to be easily integrated into portable electronic devices, such as laptops, smart phones, healthcare devices, etc. Abstract : A soft human–machine interface based on Archimedes spiral electrode and triboelectric patterns acts for self‐powered motion detection. This is a new type of self‐powered electronic skin as a motion sensor, from the analysis of the principle of triboelectric signal to simulation, and from the design of the structure to the actual test application.